Pengembangan Media Pembelajaran Kvisoft Flipbook Maker berbasis Pendekatan Problem Based Learning pada Materi Bangun Datar di Kelas IV Sekolah Dasar - Ikhwal, Herbi; Muhammadi, Muhammadi (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2025)
This research was conducted because technological advances in learning media are increasingly sophisticated and diverse. Kvisoft Flipbook Maker is an application that allows you to create interesting learning media using materials, images, videos, music, and animations that will inspire students to learn. Development (R&D) with the ADDIE model is the type of research used. The steps of the research process in the ADDIE model include analysis, design, development, implementation and evaluation. Data were collected based on validation questionnaires from material, language, and media experts, as well as practicality questionnaires from teacher and student feedback. The results of the media validity test were 90%, material 83.7%, and language 98% in the very valid category. While the results of the teacher questionnaire were 92.48% and the student questionnaire 94.46% in the very practical category at the trial school. Furthermore, the results of the teacher questionnaire were 96.42% and the student questionnaire 95.64% in the very practical category at the research school. Thus, it is concluded that Kvisoft Flipbook Maker as a learning media for Flat Building material in grade IV of integrated elementary schools is valid and practical.